Physical properties of star clusters in the outer LMC as observed by the DES. Issue 1 (26th May 2016) - Pieres, A.; Santiago, B.; Balbinot, E.; Luque, E.; Queiroz, A.; da Costa, L. N.; Maia, M. A. G.; Drlica-Wagner, A.; Roodman, A.; Abbott, T. M. C.; Allam, S.; Benoit-Lévy, A.; et al.
Abstract: The Large Magellanic Cloud (LMC) harbours a rich and diverse system of star clusters, whose ages, chemical abundances and positions provide information about the LMC history of star formation. We use Science Verification imaging data from the Dark Energy Survey (DES) to increase the census of known star clusters in the outer LMC and to derive physical parameters for a large sample of such objects using a spatially and photometrically homogeneous data set. Our sample contains 255 visually identified cluster candidates, of which 109 were not listed in any previous catalogue. We quantify the crowding effect for the stellar sample produced by the DES Data Management pipeline and conclude that the stellar completeness is <10 per cent inside typical LMC cluster cores. We therefore reanalysed the DES co-add images around each candidate cluster and remeasured positions and magnitudes for their stars. We also implement a maximum-likelihood method to fit individual density profiles and colour–magnitude diagrams. For 117 (from a total of 255) of the cluster candidates (28 uncatalogued clusters), we obtain reliable ages, metallicities, distance moduli and structural parameters, confirming their nature as physical systems. The distribution of cluster metallicities shows a radial dependence, with no clusters more metal rich than [Fe/H] ≃ −0.7 beyond 8 kpc from the LMC centre. The age distribution has two peaks at ≃1.2 and ≃2.7 Gyr.